The Relationship Between Self Compassion and Stress of the Elderly Who are Treated in Nursing Homes - Dyah Vierdiana; Amin Aji Budiman; Nadya Puspita Adriana (LPPM Universitas Harapan Bangsa, 2024)
The prevalence of mental disorders is high in the elderly category, where it contains 8.9%. Stress is one of the issues that the elderly suffer. A trigger such as the living environment suppress the elderly's feelings of stress. To reduce stress, older ones can increase their individual's self-compassion. Therefore, this study aims to determine the relationship between self-compassion and stress levels in elderly people in nursing homes. This research uses quantitative methods, namely the correlation type. The instrument used to measure self-compassion is the Adaptation Self-Compassion Scale (SCS) and the stress level instrument is the Perceived Stress Scale. The sample for this research consisted of 50 respondents. The data analysis technique uses correlation coefficient analysis. The research results show that there is a significant relationship between self-compassion and stress for elderly people in nursing homes.